Recognizing the real threat of biological terror. - Wenzel, Richard P. (American Clinical and Climatological Association, 2002)
Weapons of mass destruction can be used to harm and terrorize populations. Such weapons include those with chemical, nuclear or biological properties. Obviously computer viruses can add additional barriers to a quick response. The most effective, least costly and greatest threats are biologicals. Biological terror is not new, and biological weapons have been used for centuries. However, as a result of modern technology, the risks are greater now and the outcomes more terrible. Today they include live pathogens, various toxins, and theoretically "bioregulators"--biochemicals affecting cell signaling. Altered cell signaling could be used to induce apoptosis-cell death, or a heightened outpouring of cytokines mimicking overwhelming sepsis, or even an intracellular, biochemical "strike" causing cellular paralysis. Biological weaponeers now have the frightening ability to alter the genetic makeup of pathogens, rendering them resistant not only to available antibiotic therapy but also to currently effective vaccines. In dark corners of some fringe groups, bioweaponeers are searching for the capability of designing pathogens that target specific races, by virtue of discriminating ligands (1). The resulting morbidity and mortality from use of any biological weapons will be accompanied by chaos, governmental and social instability, panic, an extraordinary utilization of available resources, and an ongoing epidemic of sleepless nights (2,3). Herein I will review some of the issues and some of the currently available biological weapons. The major goal is to highlight the clinical presentations of patients with infections that could be used as biological weapons.